Peningkatan kemampuan representasi matematis siswa menggunakan model problem based learning - Arti Maryanti; Putra, Harry Dwi; Yuspriyati, Devi Nurul (IKIP Siliwangi, 2025)
The purpose of this study is to determine the improvement of students' mathematical representation ability after applying the Problem Based Learning (PBL) Model in junior high school students. The research method used is a quasi-experimental research with a Control Group Pretest-Posttest Design. The sample of this study consisted of 30 students in the experimental class and 30 in the control class. The sample in this study was taken by simple random sampling. Data collection was used using a mathematical representation ability test sheet. The data analysis techniques used are the N-Gain test, and the independent t-test. The results of the study were obtained: (1) The application of the PBL model can improve the ability of mathematical representation with an average N-Gain value of 0.43 which is classified as